2017
DOI: 10.1017/s1041610217001892
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects ofGinkgo bilobaextract EGb 761® on the spectrum of behavioral and psychological symptoms of dementia: meta-analysis of randomized controlled trials

Abstract: Background:In randomized controlled trials, Ginkgo biloba extract EGb 761 ® has been found to be effective in the treatment of behavioral and psychological symptoms of dementia (BPSD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
3
49
0
3
Order By: Relevance
“…Finally, a new meta‐analysis by Savaskan et al investigated the effects of EGb 761 ® on specific BPSD symptoms in patients with AD, VaD, or AD + CVD. The pooled analysis revealed significant superiority of EGb 761 ® over placebo in total scores and in ten single‐symptom scores.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a new meta‐analysis by Savaskan et al investigated the effects of EGb 761 ® on specific BPSD symptoms in patients with AD, VaD, or AD + CVD. The pooled analysis revealed significant superiority of EGb 761 ® over placebo in total scores and in ten single‐symptom scores.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the improvement of symptoms present at baseline, the risk of developing new symptoms was decreased with EGb 761 ® . Caregiver distress was also reduced …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Ihl et al, treatment of 404 patients having AD or vascular dementia with standardized extracts of Ginkgo, popularly known as EGb 761, resulted in a considerable enhancement in cognitive function and neuropsychiatric symptoms [83]. Of late a study by Savaskan et al, involving 1,628 patients with dementia, also showed the improvement of behavioral and psychological symptoms of dementia (except psychotic-like features) and caregiver distress caused by such symptoms by the administration of 22-24 weeks' treatment with EGb 761 [84]. Recent studies have also shown the use of EGb761 in providing an appropriate environment to induce differentiation of stem cells into nerve cells, which opens new and fascinating avenues for stem cell treatment of neurodegenerative diseases [85].…”
Section: Ginkgo Biloba (Ginkgo)mentioning
confidence: 99%